Advances in assembled micro- and nanoscale mechanical contact probes - Mead, James L.; Klauser, Waldemar; von Kleist-Retzow, Fabian; Fatikow, Sergej (Frontiers in Mechanical Engineering, 2022)
The micro- and nanoscale characterization and mapping of surface properties and surface behaviour is critical to both physical and biological science. Mechanical contact probes are a critical tool for investigating surface and interface science, and have seen greater development and a diversification in recent years. In particular, mechanical contact probes that have been fabricated from the bottom-up by the assembly of synthesized nano- or microscale materials can provide enhanced functionality and sensitivity over tradition microcantilevers. This work provides an overview of recent developments in the field of assembled micro- and nanoscale mechanical contact probes, with a specific focus on three probe types: colloidal particle probes with high aspect ratio and a high lateral sensitivity, one-dimensional probes comprising of nanotube and/or nanowire deflection elements, and liquid metal-based probes. For each probe type, the state-of-the-art is reviewed, and their assembly, design, functionality and capabilities are discussed. An outlook on the future direction of probe development and potential applications is also given.